Implementasi Pembelajaran Berbasis Proyek (Project-Based Learning) terhadap Penguasaan Materi Sejarah Kebudayaan Islam di MTs Hidayatul Mubtadiin Tahun Pelajaran 2025/2026: Penelitian - Lutfi Afifah, Ahsena; Aryanto, Fahri; Julaeha, Eha; Pujianti, Etika (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to analyze the implementation of Project-Based Learning (PjBL) in mastering Islamic Cultural History (SKI) materials at MTs Hidayatul Mubtadiin during the 2025/2026 academic year. The research employs a descriptive qualitative method, with data collection techniques including interviews, observations, and documentation. The results of the research show that Project Based Learning (PjBL) has proven effective in improving mastery of Islamic Cultural History material at MTs Hidayatul Mubtadiin. Apart from improving students' conceptual understanding, this method also helps develop important skills, such as critical thinking, creativity and collaboration. However, to optimize the implementation of PjBL, support is needed in the form of teacher training and improving supporting facilities. This research recommends the application of the PjBL method to other subjects to support more innovative and relevant learning.